Identifying Points of Prevention in Firearm-Related Suicides: A Mixed-Methods Study Based on Coronial Records. Issue 4 (2nd October 2022) - Faulkner, Agatha; Ogeil, Rowan P.; Stojcevski, Victor; Scott, Deborah
Abstract: Purpose: Firearm-related suicide is a noteworthy and preventable public health issue that has drawn limited attention in Australian research. Firearms are highly lethal and remain in the top three methods of suicide among Australian males. This study examines suicides occurring in Tasmania, the jurisdiction with the highest rate of firearm-related suicide, with the aim of aiding suicide prevention strategies. Methods: A mixed-methods approach was used to analyze data from the Tasmanian Suicide Register. The quantitative analysis examined socio-demographic factors, substance use, physical and mental health, and access to services for suicides occurring between January 1, 2012 and December 31, 2016. The qualitative analysis comprised firearm-related suicides occurring between January 1, 2012 and December 31, 2017. Results: Firearms users were more likely than those employing other means of suicide to be male, retired, and residing in remote areas but were less likely to have had a previous mental illness diagnosis or evidence of suicidal ideation or self-harming behaviors. There was some evidence of increased impulsiveness among firearm users. We found 54% of decedents were licensed to own a firearm at the time of death. Firearms most often belonged to the decedent (52%) and 26% sourced a firearm from family or friends. Only 58% of cases involved a firearm with a dedicated storage facility. Conclusions: Prevention efforts need to take into account the unique profiles of those at risk of firearm-related suicide. Impulsiveness and the varying levels of adherence to firearms safety practices point to the need for strategies that limit physical access to firearms. HIGHLIGHTS: Firearms-related suicides have a unique risk profile compared with other means of suicide. Mental illness diagnosis, suicidal thoughts, and self-harming behaviors were less commonly identified among firearms-related suicides than other means of suicide. Impulsiveness and the varying levels of adherence to firearms safety practices point to the need for strategies that limit physical access to firearms.